Виктор Недески - Теофилактовото „Обраќање за обвиненијата против Латините“ - Nedeski, Viktor (Филозофски факултет Скопје, 2022)
Among the many writings of Theophylact of Ohrid is his Address to one of his disciples on the charges against the Latins. In this work, the Archbishop of Ohrid presents his views on current dogmatic and ritual issu es and problems that existed in his time between the Byzantine East and the Latin West. In addition to more precise dating of this work, this study aims to present the original theological thoughts of Theophylact, which differ dramatically from the views of most of his contemporaries in the East. Be cause inter-confessional dialogue is particularly relevant today, many of the practical solutions Theophylact offers to his contemporaries may serve as a model for resolving contemporary open theological issues.
Keywords: Theophylact of Ohrid, Latins, theological disputes.